XVIII World Congress of Sociology : “Facing an unequal world: Challenges for Global Sociology” - RC51 Sessions, Yokohama 2014 (Journal of Sociocybernetics, 2013)
Call for Papers:XVIII World Congress of Sociology : “Facing an unequal world: Challenges for Global Sociology”, Yokohama, Japan, 13-19 July 2014For more details regarding the sessions organised by RC51 please have a look on   the official ISA-Website and for more detailed information: the RC51-Website If you have questions about any specific session, please feel free to contact the Session Organizer for more information, and please consider the deadline for on-line abstracts submission: September 30, 2013 24:00 GMT.